2003
DOI: 10.1074/jbc.m306914200
|View full text |Cite
|
Sign up to set email alerts
|

Caspase 3-mediated Proteolysis of the N-terminal Cytoplasmic Domain of the Human Erythroid Anion Exchanger 1 (Band 3)

Abstract: The N-terminal cytoplasmic domain of the anion exchanger 1 (AE1 or band 3) of the human erythrocyte associates with peripheral membrane proteins to regulate membrane-cytoskeleton interactions, with glycolytic enzymes such as glyceraldehyde-3-phosphate dehydrogenase and aldolase, with the protein-tyrosine kinase p72 syk , with hemoglobin and with hemichromes. We have demonstrated that the N-terminal cytoplasmic domain of band 3 (CDB3) is a substrate of the apoptosis executioner caspase 3 (1). CDB3 has two non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
16

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 49 publications
5
72
0
16
Order By: Relevance
“…This same peptide activates caspase 3 in the RBC (7,27), which cleaves the NH 2 -terminal end of band 3 (27). The inhibition of ATP release does not involve a decrease in glycolysis or the inhibition of the signal transduction pathway responsible for the release of ATP.…”
Section: Effect Of Atp On Blood Pressure (Bp)mentioning
confidence: 99%
“…This same peptide activates caspase 3 in the RBC (7,27), which cleaves the NH 2 -terminal end of band 3 (27). The inhibition of ATP release does not involve a decrease in glycolysis or the inhibition of the signal transduction pathway responsible for the release of ATP.…”
Section: Effect Of Atp On Blood Pressure (Bp)mentioning
confidence: 99%
“…Caspases comprise a family of cysteine endopeptidases expressed in erythrocytes. 47,48 However, the role of caspases during stress-induced programmed erythrocyte death seems to be more complex. Oxidative stress 47 and erythrocyte aging 48 obviously lead to stimulation of caspase-3 and degradation of target proteins, for example, erythrocyte anion exchanger 1 (band 3), while caspases are not activated after hyperosmotic shrinkage 7 or ionomycin treatment.…”
Section: -43mentioning
confidence: 99%
“…47,48 However, the role of caspases during stress-induced programmed erythrocyte death seems to be more complex. Oxidative stress 47 and erythrocyte aging 48 obviously lead to stimulation of caspase-3 and degradation of target proteins, for example, erythrocyte anion exchanger 1 (band 3), while caspases are not activated after hyperosmotic shrinkage 7 or ionomycin treatment. 2 Thus, to the extent that calcium activates the enzymes responsible for the breakdown of membrane phosphatidylserine asymmetry and degradation of the cytoskeleton, an increase of cytosolic Ca 2 þ activity is expected to trigger the clearance of the affected erythrocytes.…”
Section: -43mentioning
confidence: 99%
“…113 First, it was observed that activated caspase-3 can be detected in old, but not in young red blood cells; 114 second, this activated caspase-3 is able to cleave cell membrane band 3, disrupting its interaction with the peripheral membrane protein 4.2. 115 According to these observations, it was suggested that some caspases activated during red cell aging could participate in the degradation of crucial erythrocyte membrane proteins involved in the maintenance of shape and function. In line with these findings, it was observed that a loss of band 3 is associated with premature erythroid cell death (dyserythropoiesis).…”
Section: Apoptotic Mechanisms In Mature Red Blood Cellsmentioning
confidence: 99%